Analisis Visual Film “Kamen Rider Black Sun” dengan Pendekatan Semiotika Visual - Muhammad Iqbal Syaher; Jupriani Jupriani (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2026)
One of the countries that has developed in the field of cinema is Japan. Japan has successfully integrated elements of local culture and tradition into movie production. Japan is also famous for the creation of special effects, especially in today's modern action genre known as Tokusatsu. One of the movies that raised the Tokukatsu genre is Kamen Rider Black Sun. It is a Japanese superhero franchise Tokusatsu genre film released on October 28, 2022 by Ishimori Productions and Toei Company. The movie was directed by Kazuya Shiraishi. Based on 704 votes on IMDb.com. The movie was released in celebration of 50 years of Kamen Rider and 35 years of Kamen Rider Black. This success was based on a complex story and was well received by audiences and film critics in Japan and also abroad, including Indonesia. Visual analysis is used in this movie to interpret important elements by revealing meanings and messages that will influence the audience's understanding, especially by raising social issues. By promoting this film, it aims to raise awareness and empathy towards the phenomenon of discrimination and racism towards others. With the semiotic analysis of Roland Barthes, the film Kamen Rider Black Sun can understand the meaning of the visual signs conveyed in the film, so that this film becomes an important lesson in creating a fair society regardless of one's race, ethnicity and background.